Parallel manipulator for auto tracking system: virtual prototyping using LabVIEW- Solidworks - Ramli, Zalifah; Abdul Muthalif, Asan Gani; Shafie, Amir Akramin; Antong, Hasmawati (Trans Tech Publications, Switzerland, 2012)
Free-space optics (FSO) communication is a technology that uses light to transmit data through free space. The most important in FSO communication is the alignment between transmitter and receiver telescope. However, since the transmission medium of FSO is atmosphere, it will give misalignment between transceivers. Hence, tracking system is required to solve the problem between the transmitter and receivers. The 3-RPS parallel manipulator has been designed as a tracking system for the alignment between transceivers. First, a prototype of the system is designed in SolidWorks and integrated with LabVIEW software to perform virtual prototyping. Then, the result of virtual prrotyping is discussed